Tajweed Science Learning (Case Study on Khodijah Study Groupat Al Qur’an House An-Nazhifah Padang City) - Harahap, Mhd Tanwir Klub; Natsir, Mhd. (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This research is motivated by the uniqueness of the Khodijah study group, which has been going on for more than three years by showing high learning motivation from the students. This study aims to find out in depth various aspects of tajwid science learning activities, including: (1) formulation of learning objectives, (2) use of learning methods, and (3) evaluation of learning. The research method used is a qualitative approach with a case study design. The sampling technique uses snowball sampling. Data collection techniques use observation, in-depth interviews, and documentation analysis. The research findings show that educators have applied the principles of adult learning to the Khodijah study group learning as seen from: (1) formulation of learning objectives, (2) use of learning methods, and (3) evaluation of learning. The conclusion in this study is that educators have applied the principles of adult learning as seen from the planning of learning objectives, use of learning methods, and evaluation of learning.